Thymic and extrathymic contributions to T helper cell function in murine neonates (Hematology Meeting Reports, 2009)
Murine neonatal CD4+ responses are often biased to Th2 function. There is increasing evidence that this phenomenon may be regulated both at the level of the thymus and the peripheral lymphoid compartment. In particular, residual fetal influence on the neonatal thymus may lead to an imprinting of developing T cells that is maintained in CD4+ cells when they emigrate to peripheral organs. Such imprinting may involve epigenetic modification of the Th2 cytokine gene locus and acquisition of the capacity to undergo rapid cell cycling. These properties, coupled with the homeostatic proliferation occurring in the peripheral tissues of neonates, shape a CD4+ population with the capacity for enhanced Th2 responsiveness.